ОПТИМИЗАЦИЯ РОСТОВЫХ ПРОЦЕССОВ ХЛОРЕЛЛЫ И СПИРУЛИНЫ И ИСПОЛЬЗОВАНИЕ ЧИСТЫХ ЭКСТРАКТОВ В КАЧЕСТВЕ БИОЛОГИЧЕСКИ АКТИВНЫХ ДОБАВОК К КОРМАМ РЫБ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
Described work on optimizing of breeding processes of blue-green and green water-plants on the example of spirulina and хлореллы. An optimal environment for growing ofpresent stamm of хлореллы, and optimal concentration of cages and duration of growing is found for spirulina. The increase of culture is also well-proven the experienced way at the permanent bubbling by oxygen. On present methodologies amino acid composition of хлореллы and amount of clean albumen was certain in spirulina. All data were treated and presented in a table form.